Fingerspelling as a Novel Gateway into Reading Fluency in Deaf Bilinguals - Stone, Adam; Kartheiser, Geo; Hauser, Peter C.; Petitto, Laura-Ann; Allen, Thomas E. (PloS one, 2015)
Studies have shown that American Sign Language (ASL) fluency has a positive impact on deaf individuals' English reading, but the cognitive and cross-linguistic mechanisms permitting the mapping of a visual-manual language onto a sound-based language have yet to be elucidated. Fingerspelling, which represents English orthography with 26 distinct hand configurations, is an integral part of ASL and has been suggested to provide deaf bilinguals with important cross-linguistic links between sign language and orthography. Using a hierarchical multiple regression analysis, this study examined the relationship of age of ASL exposure, ASL fluency, and fingerspelling skill on reading fluency in deaf college-age bilinguals. After controlling for ASL fluency, fingerspelling skill significantly predicted reading fluency, revealing for the first-time that fingerspelling, above and beyond ASL skills, contributes to reading fluency in deaf bilinguals. We suggest that both fingerspelling--in the visual-manual modality--and reading--in the visual-orthographic modality--are mutually facilitating because they share common underlying cognitive capacities of word decoding accuracy and automaticity of word recognition. The findings provide support for the hypothesis that the development of English reading proficiency may be facilitated through strengthening of the relationship among fingerspelling, sign language, and orthographic decoding en route to reading mastery, and may also reveal optimal approaches for reading instruction for deaf and hard of hearing children.